ANALYZING CULTURAL AMBIVALENT IDENTITIES AND TRANSITIONAL PHASES UNDER THE INFLUENCE OF IMPERIALISM PRESENTED IN ANITA DESAI’S VOICES IN THE CITY - Zubair, Hassan Bin; Shaber, Nelofir; khadam, Iqra (Humanities & Social Sciences Reviews, 2020)
Purpose of the study: This research explores Anita Desai’s Voices in the City from the cultural ambivalence and cultural imperialism aspects. Anita Desai’s Voices in the City (1964) is about the story of an archetypal Indian protagonist Nirode and his family. Methodology: This research is qualitative. Theories presented by Homi K. Bhabha and K. R. Lyenger support this research study as a major theoretical framework. This research is based on textual analysis.It discusses the issues of the remains of colonization and the impact of British imperialism during the transitional phase of the socio-cultural and socio-political situation of Indian society that reflects the ambivalent identity of the protagonist and other characters as well. Main Findings: Nirode is a colonial subject who distinctly observes the city of Calcutta and tends to escape from such cultural tendencies of modern Indian cultures and British cultures which causes his identity ambivalent. Nirode’s position as a victim and resistant to both cultures, his subject is determined amidst the socio-cultural, socio-economic, and socio-political power relations played by both British and Indian institutional cultural values and practices of the transitional phase of Indian society that creates ambivalent identity in the life of the protagonist and other characters which happens around the city of Calcutta. Applications of the study: The research is a contribution to the existing theories on one hand and an explanation and impact of the cultural ambivalence and cultural imperialism on Indian literature and society as depicted in the novel. Novelty/Originality of the study: This research is novel as it investigates socio-cultural, socio-economic, and socio-political power relations played by both British and Indian institutional cultural values and practices of the transitional phase of Indian society that creates ambivalent identity in the life of the protagonist and other characters which happens around the city of Calcutta. The theoretical framework is taken from two different theories in order to draw more argumentative discussion.